Dyssynchrony Assessment with Tissue Doppler Imaging and Regional Volumetric Analysis by 3D Echocardiography Do Not Predict Long-Term Response to Cardiac Resynchronization Therapy. (6th December 2010) - Kuppahally, Suman S.; Fowler, Michael B.; Vagelos, Randall; Wang, Paul; Al-Ahmad, Amin; Hsia, Henry; Liang, David
Abstract : Background . Currently there are no reliable predictors of response to cardiac resynchronization therapy (CRT) before implantation. We compared pre-CRT left ventricular (LV) dyssynchrony by tissue Doppler imaging (TDI) and regional volumetric analysis by 3-dimensional transthoracic echocardiography (3DTTE) in predicting response to CRT. Methods . Thirty-eight patients (79% nonischemic cardiomyopathy) with symptomatic heart failure who underwent CRT were enrolled. Clinical and echocardiographic responses were defined as improvement in one NYHA class and reduction in LV end-systolic volume by ≥15% respectively. Functional status was assessed by Minnesota Living with Heart Failure questionnaire and 6-minute walk distance. Results . In 33 patients, after CRT for 7.86 ± 2.27 months, there were 24 (73%) clinical and 19 (58%) echocardiographic responders. Functional parameters, LV dimensions, volumes and synchrony by TDI and 3DTTE improved significantly in responders. There was no difference in the number of responders and nonresponders when cut-off values for dyssynchrony by different measurements validated in other trials were applied. Area under receiver-operating-characteristic curve ranged from 0.4 to 0.6. Conclusion . CRT improves clinical and echocardiographic parameters in patients with systolic heart failure. The dyssynchrony measurements by TDI and 3DTTE are not comparable and are unable to predict response to CRT.